Attenuated cortisol reactivity to psychosocial stress is associated with greater visual dependency in postural control. (June 2019) - Smyth, N.; Flynn, M.; Rajcani, J.; F Hucklebridge, M.; Thorn, L.; Wood, C.; Golding, J.; Evans, P.; Clow, A
Highlights: HPA-axis activity related to vestibular function in healthy participants. Attenuated cortisol reactivity related to visual dependency in postural control. Non-clinical differences in vestibular function is related to HPA axis dysfunction. Abstract: Despite known anatomical links between the hypothalamic-pituitary-adrenal (HPA) axis and the vestibular system, there are no studies on the relationship between postural control and HPA axis function. Visual dependence in postural control, often measured by increased postural sway on exposure to visual motion, is an indication of altered visual-vestibular integration with greater weighting towards visual cues for balance. Visual dependence is more common in older age and a range of vestibular and non-vestibular health conditions. The relationship between visual dependence in postural control was investigated in relation to cortisol reactivity to psychosocial stress (using the Trier Social Stress Test for groups: TSST-G), as an index of HPA axis function, in healthy young females. In those who exhibited a cortisol response (>2 nmol/l), a negative relationship between stress-induced cortisol reactivity and visual dependence in postural control was observed, since those with the largest cortisol response showed less visual motion induced postural sway (measured by force platform). This finding in healthy females indicates that subtle non-clinical differences in vestibular function are associated with dysregulated HPA axis activity as indicated by lower cortisol reactivity to psychosocial stress. It adds to the growing body of evidence linking blunted cortisol reactivity to stress to poor homeostatic regulation and potential negative health and behavioural outcomes.